Exergy and economic analyses of CCP system using full capacity of steam production and waste heat recovery in Kurdistan petrochemical complex - Abbas Naderi Pak; Mansour Lahonian; Hooshyar Mirzaei; Saman Aminian; Leyla Ranjbari (SN Applied Sciences, 2023)
Abstract The objective of this study is to analyze a combined cooling and power system from both exergy and economic perspectives, taking into account low-, medium-, and high-pressure steams. The system configuration consists of various components, namely the boiler, tank, turbine, generator, unit referred to as 180, absorption chiller, and separator. The high- and medium-pressure steams are utilized to generate power in the chiller turbine. Additionally, the low-pressure steam, which is discharged from the turbines and recycled from different sections of the system, is used to provide heat for the absorption chillers and cool the water used in the production line, thereby reducing the capacity requirements of the wet cooling towers. Among the available options, the turbine with a cost of 300 €/kW proves to be the most suitable choice for the proposed system. The results indicate that increasing the generator temperature from 65 °C to 90 °C leads to an increase in the coefficient of performance (COP) from 0.67 to 0.77. Moreover, the COP, power production, turbine efficiency, and total exergy efficiency of the proposed system are determined as 0.73, 5000 kW, 16,876 kW, 35.98%, and 57%, respectively. Ultimately, by implementing the proposed system, the product's production has been enhanced by 7% while generating an additional 16 MW of power, which represents a significant capacity for the Kurdistan Petrochemical Complex.